ANALISIS POLA PEMBELIAN PRODUK PADA E-COMMERCE PANENMART - Tsalis Kurniawan Husain; Farizah Dhaifina Amran (Politeknik Negeri Lampung, 2020)
The purpose of this study was to determine and analyze the purchase patterns of products on Panenmart e-commerce. The basic method used is the experimental method. The sampling technique in this study is saturation sampling. The data used in the study were sourced from secondary data obtained from shopping transaction data of the sales transaction database on the website and the Panenmart’s mobile application. To determine the pattern of product purchase association rules, Market Basket Analysis (MBA) is used based on three metrics, namely support, confidence and lift ratio. This study used a minimum value of support of 0.1 and a minimum value of confidence of 0.3. The results showed 3 patterns of product purchase association rules that have a strong and valid relationship to be purchased simultaneously because they had a confidence value of more than 0.3 and lift ratio value > 1. The product items had a rule pattern namely, cayenne pepper à green bean, corn à spinach, and spinach à green bean.